7SL RNA Is Retained in HIV-1 Minimal Virus-Like Particles as an S-Domain Fragment - Keene, Sarra E. (American Society for Microbiology (ASM), 2010)
HIV-1 is known to package several small cellular RNAs in addition to its genome. Previous work consistently demonstrated that the host structural RNA 7SL is abundant in HIV-1 virions but has yielded conflicting results regarding whether 7SL is present in minimal, assembly-competent virus-like particles (VLPs). Here, we demonstrate that minimal HIV-1 VLPs retain 7SL RNA primarily as an endoribonucleolytic fragment, referred to as 7SL remnant (7SLrem). Nuclease mapping showed that 7SLrem is a 111-nucleotide internal portion of 7SL, with 5′ and 3′ ends corresponding to unpaired loops in the 7SL two-dimensional structure. Analysis of VLPs comprised of different subsets of Gag domains revealed that all NC-positive VLPs contained intact 7SL while the presence of 7SLrem correlated with the absence of the NC domain. Because 7SLrem, which maps to the 7SL S domain, was not detectable in infected cells, we propose a model whereby the species recruited to assembling VLPs is intact 7SL RNA, with 7SLrem produced by an endoribonuclease in the absence of NC. Since recruitment of 7SL RNA was a conserved feature of all tested minimal VLPs, our model further suggests that 7SL's recruitment is mediated, either directly or indirectly, through interactions with conserved features of all tested VLPs, such as the C-terminal domain of CA.